THE IMPORTANCE OF CEARÁ STATE TO THE BRAZILIAN MARINE ORNAMENTAL FISH EXPORTS - de Gurjão, Lívio Moreira; Lotufo, Tito Monteiro da Cruz (Arquivos de Ciências do Mar, 2018)
Brazil is one of the main suppliers of marine aquarium fish in the world and Ceará state is the most relevant trader in the country. However, there is a paucity of updated information regarding the activity, which is crucial for the sustainable exploitation of those organisms. Thus, the present work provides the most recent data related to Brazilian and, more specifically, Ceará state marine aquarium fish exports, by means of the analysis of information from 420,871 authorizations of export issued by Brazilian environmental authorities in the last 10 years. Results corroborate the relevant participation of Ceará state in the Brazilian marine ornamental fish trade, but also show a substantial decline of exports along the last decade. Sixteen species were the most abundant and more frequently traded. Unsurprisingly, pomacanthids were the most important exported fish, and probably more than 283,525 individuals were wild-caught in an almost 10-years interval. Current Brazilian exports are mainly driven to Asian countries and seasonal displacements of the Intertropical Convergence Zone (ITCZ) seems to influence ornamental fish harvesting in Ceará state, impacting significantly the Brazilian performance in the trade.